The role of providing adequate support for the use of information technology in improving the quality of accounting information systems (Economic studies journal, 2025)
The current study aimed to identify the role of information technology in improving the quality of accounting information systems, and the availability of sufficient support for their use. This is through the use of information technology in producing and disseminating accounting information that can improve the accuracy and comprehensiveness of this information and facilitate the process of disclosing it. The study sought to evaluate the availability of information technology infrastructure in accounting information systems in Libyan companies. The study population was represented by the General Electricity Company, and the study sample represented employees in the financial and accounting departments in the offices of the General Electricity Company in the southern region. The number of members of the study sample reached 50 individuals, and they were the ones who answered the questions of the questionnaire, which were chosen using the simple random sampling method. The descriptive analytical method was used. The most important results demonstrated the availability of information technology infrastructure in companies and the effectiveness of using information technology in accounting information systems. The study concluded with a set of recommendations, the most important of which is working to increase institutions’ investment in information technology to keep pace with technological developments and improve the efficiency of their accounting information.
Keywords: Information technology; Accounting information systems; The world of finance and business; General electricity company